The cyclonic Swami : Vivekananda in the West - Sengupta, Sukalyan; Paranjape, Makarand R.; Samvad India; University of Massachusetts Dartmouth. Center for Indic Studies (New Delhi : Samvad India Foundation, in association with Center for Indic Studies, University of Massachusetts at Dartmouth, 2005)
Contributed articles.
Includes bibliographical references.
Keywords: VIVEKANANDA, -- SWAMI, -- 1863-1902.